1997
DOI: 10.1172/jci119274
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged endothelin A receptor blockade attenuates chronic pulmonary hypertension in the ovine fetus.

Abstract: Based on past studies of an experimental model of severe intrauterine pulmonary hypertension, we hypothesized that endothelin-1 (ET-1) contributes to high pulmonary vascular resistance (PVR), hypertensive lung structural changes, and right ventricular hypertrophy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 51 publications
4
72
2
Order By: Relevance
“…Our results in the neonate are similar to the ones reported in the adult rat, in which BQ-123 and the nonpeptidic ET antagonists, bosentan and TBC11251, were able to reverse hypoxia-induced pulmonary hypertensive changes (22,25,26). A previous demonstration in an ovine fetal preparation had also shown that preventive treatment with BQ-123 could attenuate chronic pulmonary hypertension (27).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results in the neonate are similar to the ones reported in the adult rat, in which BQ-123 and the nonpeptidic ET antagonists, bosentan and TBC11251, were able to reverse hypoxia-induced pulmonary hypertensive changes (22,25,26). A previous demonstration in an ovine fetal preparation had also shown that preventive treatment with BQ-123 could attenuate chronic pulmonary hypertension (27).…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, treatment with TBC3711 may help to counteract some, but not all, of these mechanisms. Although Ivy et al (27) have described improvement of right ventricular hypertrophy after 8 d of preventive treatment with BQ-123 in an ovine model of pulmonary hypertension, complete reversal of right ventricular hypertrophy in our model may take longer. Furthermore, it is unknown, in our model, how the pharmacologic recovery compares with the rate of recovery once exposure to hypoxia is terminated.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The physiologic role of ET-1 in the fetus and newborn is unclear. Some studies of fetal animals point to a principally vasodilatory action (15,26,27), whereas others favor a predominantly vasoconstrictive effect (14,16). We have previously reported high plasma levels and strong pulmonary expression of ET-1 in newborn piglets, with a fall to adult levels at 3 d of life (7,28).…”
Section: Discussionmentioning
confidence: 96%
“…45 A Cochrane review of this class of drugs in conjunction with conventional therapy has shown that it can improve the clinical outcomes in adults with idiopathic pulmonary artery hypertension. 46 Almost no experience with ERAs exists in the neonatal population.…”
Section: Endothelin-1 Receptor Antagonists (Bosentan Sitaxsentan)mentioning
confidence: 99%